Alternative medicine studies (PAGEPress, 2011)
A peer-reviewed, open-access journal about alternative medicine systems including acupuncture, anthroposophic medicine, ayurveda, chiropractic, herbalism and natural products, homeopathy, naturopathy, osteopathy, and traditional medicines (e.g. Chinese, Tibetan).